Development and validation of the Nursing Students’ Growth Mindset Scale (NSGMS) - Cao, Meijuan; Ling, Zheyi; Xie, Chunqi; Xu, Xiaojuan (Frontiers in Medicine, 2025)
BackgroundGrowth mindset is increasingly valued for its important role in the training of nursing students. However, research on the development of tools to measure growth mindset effectively among nursing students is limited.ObjectiveTo develop a measurement tool to evaluate nursing students’ growth mindset.DesignA cross-sectional methodological study.Participants and settingA total of 271 nursing students from 4 universities or university colleges in Zhejiang and Hunan participated in the study.MethodsDomains and items of nursing students’ growth mindset were identified and created by conducting a literature review and qualitative interviews. To test the content validity, a 2-round Delphi was adopted, and a pilot implementation was conducted with 30 nursing students. The construct validity of the scale was tested using exploratory and confirmatory factor analyses (n = 206).ResultsAccording to the exploratory factor analysis results, the Kaiser–Meyer–Olkin value was 0.87, and the Bartlett test’s χ2 was 2659.680 (p < 0.05). One item with a factor loading value below 0.50 was removed from the scale, and the obtained factor structure explained 67.01% of the variance. The fit indices of the scale model tested in the confirmatory factor analysis were determined as χ2/df = 1.42, RMSEA = 0.05, CFI = 0.97, TFI = 0.97, IFI = 0.97. The scale structure was confirmed using 4 factors and 21 items. The Cronbach’s alpha values were found to be 0.77–0.90 for the subdimensions of the scale and 0.88 for the total scale. The data also showed good test–retest stability (ICC = 0.90).ConclusionThis scale is a reliable and valid measurement tool to determine nursing students’ level of growth mindset. Further studies with larger and more diverse samples are recommended to evaluate the psychometric structure of this scale.